Comparison of sand fly trapping approaches for vector surveillance of Leishmania and Bartonella species in ecologically distinct, endemic regions of Peru. - Victor O Zorrilla; Marisa E Lozano; Liz J Espada; Michael Kosoy; Clifton McKee; Hugo O Valdivia; Heriberto Arevalo; Mario Troyes; Craig A Stoops; Michael L Fisher; Gissella M Vásquez (Public Library of Science (PLoS), 2021)
Background In Peru, the information regarding sand fly vectors of leishmaniasis and bartonellosis in the Amazon region is limited. In this study, we carried out sand fly collections in Peruvian lowland and highland jungle areas using different trap type configurations and screened them for Leishmania and Bartonella DNA. Methodology/principal findings Phlebotomine sand flies were collected in Peruvian Amazon jungle and inter Andean regions using CDC light trap, UV and color LED traps, Mosquito Magnet trap, BG Sentinel trap, and a Shannon trap placed outside the houses. Leishmania spp. screening was performed by kDNA PCR and confirmed by a nested cytochrome B gene (cytB) PCR. Bartonella spp. screening was performed by ITS PCR and confirmed by citrate synthase gene (gltA). The PCR amplicons were sequenced to identify Leishmania and Bartonella species. UV and Blue LED traps collected the highest average number of sand flies per hour in low jungle; UV, Mosquito Magnet and Shannon traps in high jungle; and Mosquito Magnet in inter Andean region. Leishmania guyanensis in Lutzomyia carrerai carrerai and L. naiffi in Lu. hirsuta hirsuta were identified based on cytB sequencing. Bartonella spp. related to Bartonella bacilliformis in Lu. whitmani, Lu. nevesi, Lu. hirsuta hirsuta and Lu. sherlocki, and a Bartonella sp. related to Candidatus B. rondoniensis in Lu. nevesi and Lu. maranonensis were identified based on gltA gene sequencing. Conclusions/significance UV, Blue LED, Mosquito Magnet and Shannon traps were more efficient than the BG-Sentinel, Green, and Red LED traps. This is the first report of L. naiffi and of two genotypes of Bartonella spp. related to B. bacilliformis and Candidatus B. rondoniensis infecting sand fly species from the Amazon region in Peru.